Inhibition of Fusarium graminearum and other Fusarium species by Cochlioblolus sativus in culture and on barley plants. Issue 4 (1st October 2016) - Rampitsch, Christof; Bacala, Ray; Tekauz, Andy; McCallum, Brent D.
Abstract: The fungal pathogens Cochliobolus sativus and Fusarium graminearum are frequently isolated from diseased barley spikes in western Canada. When seeds co-infected with these two species were plated on solid nutrient media, C. sativus strongly inhibited the growth of F. graminearum and at least five other Fusarium species associated with Fusarium head blight (FHB). An inhibitory substance was secreted into the media in advance of C. sativus hyphae, creating a clear zone of inhibition which was devoid of any hyphae. The size of this zone of inhibition varied between C. sativus isolates. C. sativus inhibited F. graminearum and FHB development when it was inoculated onto spikes of 'AC Metcalfe', 'Manley' or 'Stander' barley before inoculation with F. graminearum, whereas co-inoculation or inoculation with C. sativus after F. graminearum did not reduce FHB symptoms. A putative toxic compound was enriched from a liquid culture of C. sativus and shown to retain activity in vitro . The compound was partially purified by high performance liquid chromatography and its mass determined to be 234 u by electrospray ionization mass spectrometry and gas chromatography-mass spectrometry. Results from partial characterization of the enriched toxin are consistent with prehelminthosporol and it is likely that this, or one of its derivatives, was inhibiting F. graminearum . This antibiotic compound could enable C. sativus to compete more effectively with other fungal species on both plants and in the soil.